Maternal gene expression in Atlantic halibut (Hippoglossus hippoglossus L.) and its relation to egg quality - Mommens, Maren (BioMed Central, 2010)
BACKGROUND: The commercial production of Atlantic halibut (Hippoglossus hippoglossus L.) suffers from a major bottleneck due to the low success of producing juveniles for on-growing. Atlantic halibut females are routinely hand-stripped and incorrect timing of stripping can result in low quality eggs due to post-ovulatory aging. Post-ovulatory aging leads to compositional changes in eggs that include maternally provided proteins and RNAs. There have been few studies of the maternally provided mRNA transcripts that control early development in commercially important fish species. The present study aimed to study maternal gene expression in Atlantic halibut and its relation to egg quality parameters including blastomere symmetry and hatching success. RESULTS: A maternal EST library containing 2341 sequences was constructed by suppressive subtractive hybridisation. Thirty genes were selected for expression studies; 23 novel genes and 7 genes with documented roles in early development. The expressions of twenty-one selected genes were measured by qPCR from fertilization to the 10-somite stage. Three genes were identified as strictly maternal genes that were expressed until the start of gastrulation; askopos (kop), si:dkey-30j22.9 (Tudor family member), and Tudor 5 protein (Tdrd5). The expressions of 18 genes at the 8-cell stage were correlated with egg quality parameters. The majority of genes showed either no or very minor correlations with egg quality parameter. However, two genes correlated positively with hatching success (r> 0.50, HHC00353: r = 0.58, p < 0.01; HHC01517: r = 0.56, p < 0.01) and one gene (HHC00255) was negatively correlated with the percentage of normal blastomeres (r = -0.62, p < 0.05). CONCLUSIONS: During this study we have related maternal levels of gene expression to hatching success in fish. Poor hatching success was not correlated with a general decrease in transcript abundance but with low transcript levels of some specific genes. Thus, the molecular mechanisms leading to low Atlantic halibut egg quality cannot be entirely explained by post-ovulatory aging.